Hedonic appreciation and verbal description of pleasant and unpleasant odors in untrained, trainee cooks, flavorists, and perfumers - Sezille, Caroline; Fournel, Arnaud; Rouby, Catherine; Rinck, Fanny; BENSAFI, Moustafa (Frontiers in Psychology, 2014)
Olfaction is characterized by a salient hedonic dimension. Previous studies have shown that these affective responses to odors are modulated by physicochemical, physiological and cognitive factors. The present study examined expertise influenced processing of pleasant and unpleasant odors on both perceptual and verbal levels. For this, performance on 2 olfactory tasks was compared between novices, trainee cooks and experts (perfumers and flavorists): members of all groups rated the intensity and pleasantness of pleasant and unpleasant odors (perceptual tasks). They were also asked to describe each of the 20 odorants as precisely as possible (verbal description task). On a perceptual level, results revealed that there were no group-related differences in hedonic ratings for unpleasant and pleasant odors. On a verbal level, descriptions of smells were richer (e.g. chemical, olfactory qualities and olfactory sources terms) and did not refer to pleasantness in experts compared to untrained subjects who used terms referring to odor sources (e.g. candy) accompanied by terms referring to odor hedonics. In conclusion, the present study suggests that as novices, experts are able to perceptually discriminate odors on the basis of their pleasantness. However, on a semantic level, they conceptualize odors differently, being inclined to avoid any reference to odor hedonics.